ДОМОВЫЕ ЦЕРКВИ г. АЛЕКСАНДРОВСКА НАЧАЛА ХХ ВЕКА: К ИСТОРИИ ВОЗНИКНОВЕНИЯ (по материалам Государственного архива Запорожского области) (Zaporizhzhia Historical Review, 2021)
House-church appearance in Olexandrovsk (Zaporizhzhya since 1921) in beginning XX century is considered in the clause at first. Author shows the unknown facts about house-churches in educational institution.